2023
DOI: 10.15517/psm.v21i1.53127
|View full text |Cite
|
Sign up to set email alerts
|

COVID-Inconfidentes - SARS-CoV-2 seroprevalence in two Brazilian urban areas in the fourth quarter 2020: study protocol and initial results

Abstract: Objective: To describe study protocol and initial results of research project COVID-Inconfidentes. Method: This paper described the methodological procedures adopted and the prevalence of the SARS-CoV-2 infection in the population. A household survey was conducted between October and December 2020, in two historic cities of Brazil's mining region. Anti-SARS-CoV-2 antibody was detected using the Wondfo® rapid test. The face-to-face interview consisted of administration of a questionnaire containing registration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Participants eligible for the study were permanent residents of households in the urban areas of the municipalities, aged ≥ 18 years, who consented to participate in the study. Individuals with compromised cognitive function, difficulty in responding to the questionnaire, or inability to provide blood samples due to difficulties with venous access were excluded [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants eligible for the study were permanent residents of households in the urban areas of the municipalities, aged ≥ 18 years, who consented to participate in the study. Individuals with compromised cognitive function, difficulty in responding to the questionnaire, or inability to provide blood samples due to difficulties with venous access were excluded [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sampling weight of each selected unit (census sector, household, and individual) was calculated to correlate with the 2019 population projection. For more details on the sample calculation and field logistics, see Meireles et al [ 29 ]. A total of 1789 individuals were recruited, of which 27 (1.5%) were excluded for not completing the interview or not collecting a blood sample, totaling 1762 individuals, of which 764 were from the municipality of Mariana (43.4%) and 998 from Ouro Preto (56.6%).…”
Section: Methodsmentioning
confidence: 99%
“…This study followed reported guidelines dictated by the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE). For more details on data collection, see Meireles et al 14 .…”
Section: Methodsmentioning
confidence: 99%